Trudinger-type inequalities on Musielak-Orlicz-Morrey spaces of an integral form - Ohno, Takao; Shimomura, Tetsu (MATHEMATICA SCANDINAVICA, 2022)
Our aim in this paper is to give Trudinger-type inequalities for Riesz potentials of functions in Musielak-Orlicz-Morrey spaces of an integral form over non-doubling metric measure spaces. Our result are new even for the doubling metric measure setting. As a corollary, we give Trudinger-type inequalities on Musielak-Orlicz-Morrey spaces of an integral form in the framework of double phase functions with variable exponents.